Strategi Pemasaran Roti Bakar Jamin Halal Nikmat (JHN) Wangi Madu Studi Kasus Desa Sepuk Tanjung Kacamatan Sebawi Kabupaten Sambas - Susilawati, Irma Fahrizal Butsi Ningsih, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
Bread is an additional food favored by people in Sambas Regency. One of the businesses engaged in making baked bread is